Anisotropic photogenerated charge separations between different facets of a dodecahedral α-Fe2O3 photocatalyst. Issue 42 (9th October 2019) - Wang, Conghui; Zhu, Chuanming; Ren, Xiaobo; Shi, Jing; Wang, Liancheng; Lv, Baoliang
Abstract : Hematite (α-Fe2 O3 ) is regarded as one of the most promising photocatalysts, but its photocatalytic activities have always been limited to the pristine form because of poor charge separation efficiency. Abstract : Hematite (α-Fe2 O3 ) is regarded as one of the most promising photocatalysts, but its photocatalytic activities have always been limited to the pristine form because of poor charge separation efficiency. In the present work, a new kind of dodecahedral α-Fe2 O3 particle (DoFe) enclosed by six (012) and six (104) facets provides us with a clue to solving this problem, because the coexistence of these two facets brings about a better photocatalytic performance than that for crystals exposing only a single facet. The results show that, in addition to surface structures, photogenerated charge separations between anisotropic facets also have an influence on photocatalytic activities. Furthermore, particle size could be precisely regulated, which is helpful for ruling out the possible specific contribution of edges and vertexes. These results are of great importance for our understanding of the relationship between morphology and activities, and can direct us to synthesize a high-efficiency catalyst.